2021
DOI: 10.1073/pnas.2016146118
|View full text |Cite
|
Sign up to set email alerts
|

Reversed-engineered human alveolar lung-on-a-chip model

Abstract: Here, we present a physiologically relevant model of the human pulmonary alveoli. This alveolar lung-on-a-chip platform is composed of a three-dimensional porous hydrogel made of gelatin methacryloyl with an inverse opal structure, bonded to a compartmentalized polydimethylsiloxane chip. The inverse opal hydrogel structure features well-defined, interconnected pores with high similarity to human alveolar sacs. By populating the sacs with primary human alveolar epithelial cells, functional epithelial monolayers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(119 citation statements)
references
References 62 publications
(56 reference statements)
2
108
0
Order By: Relevance
“…Some PDMS-treatments have been proposed to overcome this problem, as well as alternatives consisting of the use of hydrogels. Huang et al (2021) generated a 3D porous gelatin methacryloyl (GelMa) hydrogel, presenting an alveolar sac-like 3D structure (Figure 2D) [59]. Amongst the advantages of using GelMa instead of synthetic membranes, the stiffness (6.23 ± 0.64 kPa) is within the range reported for native lungs [65].…”
Section: Microfluidic Lung Systemsmentioning
confidence: 79%
See 2 more Smart Citations
“…Some PDMS-treatments have been proposed to overcome this problem, as well as alternatives consisting of the use of hydrogels. Huang et al (2021) generated a 3D porous gelatin methacryloyl (GelMa) hydrogel, presenting an alveolar sac-like 3D structure (Figure 2D) [59]. Amongst the advantages of using GelMa instead of synthetic membranes, the stiffness (6.23 ± 0.64 kPa) is within the range reported for native lungs [65].…”
Section: Microfluidic Lung Systemsmentioning
confidence: 79%
“…Other microfluidic lung systems modeling the alveolar region were set up in other studies, using a similar working principle [59,64]. In some of these models, the flat and synthetic porous membrane was replaced by a biological membrane containing proteins of the ECM and relevant 3D shapes, thus conferring a more physiologically relevant 3D microarchitecture and enhancing their biological performance [59,64].…”
Section: Microfluidic Lung Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously groups tended to PDMS as the scaffold of choice when developing Lung-on-a-Chip models [ 9 ]; however, due to its high Young’s modulus, hydrogels are becoming more common as they can mimic the stiffness of the lung ECM. Huang et al recently showed a GelMA based scaffold with a modulus of 6.23 ± 0.64 kPa [ 54 ].…”
Section: Scaffold Requirementsmentioning
confidence: 99%
“…This material has well-defined and interconnected pores that are highly similar to human alveolar sacs. By culturing primary human alveolar epithelial cells on the chip, the functional alveolar epithelium can be easily formed, and breathing movement can be realized [ 48 ].…”
Section: Physiological Model Of Respiratory System Based On Organ-on-a-chipmentioning
confidence: 99%